Harnessing Digital Technologies to Promote SMEs in the MENAP Region - Lukonga, Inutu (IMF Working Papers; Working Paper ;, 2020)
Policy makers in the MENAP region have been formulating policies and designing programs to develop small and medium sized enterprises (SMEs) with a view to create jobs and achieve inclusive growth. But while the programs have helped increase the number of enterprises, growth of SMEs continues to face barriers to growth. As a result, microenterprises predominate and SMEs contribution to employment remains below potential. Partial implementation of reforms explain some of the underperformance, but frictions in strategy design also played an important role. Sustaining current reforms is, therefore, not sufficient to achieve inclusive growth. Digital technologies have potential to boost SMEs productivity and growth and economies are rapidly digitalizing, thus SMEs need to embrace digital solutions to compete and survive. Therefore, for SMEs to be effective engines of inclusive growth, a rethinking of the SME development strategy is needed that makes SMEs' digital transformation a priority.